Carnival exhausted: Roguishness and resistance in W. G. Sebald. (March 2019) - Stacy, Ivan
This article examines the under-acknowledged presence of carnivalesque elements in W. G. Sebald's prose fiction. While the carnivalesque holds a less prominent position than melancholy in Sebald's work, it is nevertheless a persistent aspect, although its presence decreases in his later texts and is almost entirely absent from Austerlitz . The article argues that these elements form part of Sebald's resistant stance towards the dominant discourses of modernity. On this basis, the article discusses the carnivalesque in Vertigo, The Emigrants and The Rings of Saturn from two perspectives. First, it examines the presence of carnivalesque figures and locations, arguing that these are evidence of carnival's exhaustion, and of the way that modernity has closed down the possibility of licensed transgression. Second, it argues that the narrators themselves are duplicitous, 'masked' figures whose inconsistencies and ethical transgressions are central to Sebald's project of unbinding modern subjectivity.